2020
DOI: 10.3390/cells9030764
|View full text |Cite
|
Sign up to set email alerts
|

On the TRAIL of Better Therapies: Understanding TNFRSF Structure-Function

Abstract: Tumor necrosis factor (TNF) superfamily ligands show diverse biological functions, such as the induction of apoptotic cell death or cell survival and proliferation, making them excellent therapeutic targets for cancer and autoimmunity. We review the latest literature on TNF receptor superfamily signaling with a focus on structure-function. Using combinatorics, we argue that receptors that cluster on the cell surface and are activated by membrane-bound ligands need to arrange in a highly ordered manner, as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…21 d after injection, lung metastases were determined (G). a higher-order signaling complex mediated by TNFR-associated factor dimerization and trimerization interfaces (Napetschnig and Wu, 2013;Vanamee and Faustman, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…21 d after injection, lung metastases were determined (G). a higher-order signaling complex mediated by TNFR-associated factor dimerization and trimerization interfaces (Napetschnig and Wu, 2013;Vanamee and Faustman, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Binding of TNFα to the TNFR1 eventually leads to caspase or NF-κB activation ( Faustman and Davis, 2010 ; Brenner et al., 2015 ), whereas trimeric activation of Fas, TrailR1/2 complexes selectively induces caspase-mediated apoptosis (David R. McIlwain et al., 2015 ; E. M. Creagh and Martin, 2001 ). Recent data suggests also higher-than-trimeric receptor oligomerization upon activation ( Vanamee and Faustman, 2020 ), comparable to cluster-activation seen for T-cell receptors ( Grakoui et al., 1999 ). Targeted analysis of TNFRSF members is also of importance, because mutations in TNFSF/TNFRSF members can lead to various diseases among them, such as TNF receptor-associated periodic syndrome (TRAPS) ( Savic et al., 2012 ) or autoimmune lymphoproliferative syndrome (ALPS) (Anke M.J. Peters et al., 1999 ).…”
Section: Introductionmentioning
confidence: 78%
“…Here, we could see that apoptosis induced by FasL dimers is carried out slower than apoptosis of trimeric or hexameric FasL. Recent studies showed that Fas receptors are arranged as antiparallel dimers that form overall hexagonal lattices without the ligand (Vanamee and Faustman, 2018a;Vanamee and Faustman, 2020). This arrangement is necessary for the appropriate DISC formation and interaction with FADD upon ligand binding.…”
Section: Ll Open Access Isciencementioning
confidence: 88%
“…In general, there was a significant upregulation of genes previously demonstrated to have anti-tumor activity and downregulation of many having pro-tumor involvement. For example, TNF-related apoptosis-inducing ligand (TRAIL) is a potent stimulator of apoptosis, especially on tumor cells, making them excellent therapeutic targets for cancer ( 74 ). Cytotoxic ADMC upregulated several TRAIL receptors (e.g.…”
Section: Discussionmentioning
confidence: 99%